Menelusuri Isu dan Tren Global Kurikulum Sains melalui Pendekatan Deep Learning: Analisis Bibliometrik Terbaru - Rini Shoffa Aulia; Chaerul Rochman; Adam Malik; Tri Wahyu Agustina (Mataram University, 2026)
This study aimed to analyze current trends and emerging issues in the science curriculum through a bibliometric approach using VOSviewer software. A total of 200 recent articles from reputable internationally indexed scientific publications published between 2020 and 2025 were collected and analyzed based on the keyword “science curriculum.” The results of the co-occurrence and density visualization analyses indicate that research on the science curriculum is divided into two main clusters. The first cluster focuses on pedagogical approaches, such as inquiry-based learning, teacher roles, classroom context, and project-based learning, emphasizing the development of 21st-century skills and student learning performance. The second cluster reveals emerging trends toward the integration of technology and artificial intelligence, including artificial intelligence, computer science curriculum, and data analysis, reflecting the transformation of the curriculum toward the digital era. Overall, the bibliometric findings indicate a shift in the science curriculum paradigm from conventional approaches toward adaptive and technology-based learning, with an emphasis on the development of digital competencies, interdisciplinary collaboration, and creativity in science education. These findings highlight the importance of curriculum innovation that integrates STEM approaches and artificial intelligence (AI) literacy to address the challenges of 21st-century education.